THE MORPHOLOGICAL AND SPECIES DIVERSITY OF SPONGES ON CORAL REEF ECOSYSTEMS IN THE LEMBEH STRAIT, BITUNG - Hadi, Tri Aryono; Suharsono, -; Hadiyanto, -; Budiyanto, Agus; Wentao, Niu (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
Sponges are one of the most diverse benthos in the coral reef ecosystem. They have many morphological characters that are specific to species, and their existence is influenced by environmental conditions. The aims of this study are to observe the relationship between morphological and species diversity of sponges in coral reef ecosystem in the Lembeh Strait and investigate the most influential environmental factor on sponge diversity. The study was carried out between April and May 2013 at nine study sites. The methods used were belt transect and line intersect transect (LIT) installed parallel to the coastline at approximately 5-meter depth. Our study supports a positive correlation between the morphological diversity and species diversity of sponges. Many of the morphological growth types were specific to sites that have particular characteristics. The percentage of the live coral cover is not a critical factor for sponge diversity in the strait. Instead, dead coral with algae as a benthic category has a significant positive correlation with the morphological and species diversity of sponges. Conversely, rubble as a substrate type has a strong tendency to affect sponge diversity negatively. To conclude, it is important to maintain healthy reefs in order to sustain benthic communities that are valuable to ecological functions and societies. Keywords:sponges, diversity, coral reefs, Lembeh Strait